Effects of Lactic Acid Bacteria and Molasses Additives on Dynamic Fermentation Quality and Microbial Community of Native Grass Silage - Li, Yuyu; Du, Shuai; Sun, Lin; Cheng, Qiming; Hao, Junfeng; Lu, Qiang; Ge, Gentu; Wang, ZhiJun; Jia, Yushan (Frontiers in Microbiology, 2022)
Ensiling native grass is an effective method to protect the nutritional quality of forage and alleviate feed shortages in the cold winter of the Inner Mongolian Plateau. To improve the usability of native grass resources as feed in China, the effects of lactic acid bacteria and molasses additions on the microbial population, fermentation quality, and nutritional quality of native grass during silage were investigated. Treatments were a control treatment with no additive (CK), lactic acid bacteria (L), molasses (M), and lactic acid bacteria in combination with molasses (L+M), all of which were stored at ambient temperature (17-28 ℃) for 7, 14, 30 and 60 days. The results showed that all additives improved nutritional value and fermentation quality with low pH and ammonia nitrogen (NH3-N) and high crude protein (CP) and water soluble carbohydrate (WSC) than control silage over the ensiling period. Compared to L or M silage, the L+M silage combination improved fermentability, as evidenced by higher LA content and a faster pH drop during the first 7 days of ensiling. With prolonged ensiling time, the combined addition of L and M could increase the count of desirable Lactobacillus, decrease microbial diversity, and inhibit the growth of undesirable microorganism such as Clostridia, Escherichia and Enterobacter abundance compared with silage treated with CK, L or M. Application of L together with M could further improve the silage quality of native grass by altering bacterial community structure. In summary, the addition of lactic acid bacteria and molasses increased the relative abundance of Lactobacillus of native grass silage and improved fermentation quality.